Tabagismo e fatores associados entre pacientes dos ambulatórios do hospital universitário Júlio Muller, Cuiabá - MT, 2013 - Silva, Keyla Medeiros Maia (2013)
Among the chronic diseases , smoking has become a public health issue, and is considered by the World Health Organization as the largest preventable cause of death worldwide. Along with alcohol, presents itself as a psychoactive drug with initiation in adolescence. Among the factors associated with its use is related to the level of functioning of the family of origin. Objectives: To estimate and analyze the prevalence of smoking and its association with the general level of family functioning. Method: Cross-sectional study conducted at the University Hospital Júlio Muller, Cuiabá, Mato Grosso, from May to August 2013. Through a convenience sample was obtained, the acceptance of 671 patients in consultation in the various clinics of the university hospital. The instrument used was composed of variables biossociodemograficas, family and smoking, which is defined according to the criteria of the Ministry of Health was applied to test-retest evaluation of the Kappa coefficient to verify the reliability issues. We used the bivariate analysis using chi -square and Fisher's exact Poisson regression , with measures of association prevalence ratio with confidence interval of 95 %. Results: The prevalence of smoking was 18.2%, associated with statistically significant factor to have suffered parental physical abuse paternal (OR: 1.14, 95% CI 1.03 to 1.26), having as protective factors being female (PR: 0.90, 95% CI 0.86 to 0.94), having more than 12 years and schooling (PR: 0.99, 95% CI from 0.9909 to 0.9943), have high paternal parental responsiveness in the family (PR: 0.89, 95% CI 0.82 to 0.96), not having so-Frido physical neglect (OR: 0.81, 95% CI 0.72 to 0.91) and there have been a victim of abuse maternal physical (RP: 0.81, 95% CI 0.71-0.93). Conclusions: Cigarette smoking in this population is associated with established relationships in the family. It is suggested that the family should be considered in the implementation of preventive actions for the service and courses in Education and Health.